State of regulation and implementation of energy and water-saving measures in buildings in Colombia (2021)
This article analyzes the status of compliance with "Resolución 0549 de 2015", which regulates the parameters of sustainable construction in buildings from Colombia, in terms of energy and water consumption. Compliance with these guidelines is in line with the sustainable development goals set out in the 2030 agenda, specifically with SDGs 11, 12 and 13. Thus, the analysis of the history of public policies, which have been in line with the certifications that exist or have existed at the international level, is envisioned. The analysis of buildings with sustainable construction certificates is carried out to verify their concordance with the parameters established in the Colombian regulations. Finally, a contrast is presented between the expectations set forth in the percentage of water and energy savings indicated by the government and the actual values executed. The results show that, the new projects that have been certified as sustainable buildings, more than 50% comply with the minimum percentages of reduction in water and energy consumption.